DIGITAL LITERATION AND MULTIMODAL FOR EARLY CILDHOOD EDUCATION - Dyah Ageng Pramesty Koenarso; Aspiya Aziza (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2022)
The digital and multimodal literacy process of early childhood at TK Santa Maria and PAUD Sabilal Muhtadin Banjarmasin is carried out through watching educational films such as the Prophet's story, introducing themes, motor and art activities through the media of projectors, cellphones, laptops, and computers. These activities increase children's interest in the learning process, children establish verbal language with non-verbal modes such as gestures and facial expressions to express meaning in their interactions with others. Digital and multimodal literacy activities carried out so far are by using a display through a projector to introduce themes, sometimes children use television in the free room to watch such as religious films, exercise or dance activities and listen to songs to children. A multimodal approach to optimal literacy and collaboration with parents can provide games, and other communicative modes (gestures, movement, music, etc.).